Rudolf Schlechter's South-American orchids II. Schlechter's "network": Brazil (La Plata River Basin) - Ossenbach, Carlos (Universidad de Costa Rica, 2019)
As the second chapter of the series about Rudolf Schlechter’s South-American Orchids, a background of the orchidological work by foreign and Brazilian orchidologists in southern Brazil is outlined, as well as the history of the most important botanical institutions in this region. In order to establish coherent geographical units, the institutions, botanists and collectors mentioned in this chapter are those whose main activity concentrated in the Brazilian part of the La Plata River Basin, or in other words, the Brazilian states including and southwards of Matto Grosso, Minas Gerais and Espirito Santo. The most important figures in Schlechter’s Brazilian “network” are presented, with short biographical notes and description of their most important botanical exploits.